1996
DOI: 10.1097/00007890-199605270-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pravastatin on Acute Rejection After Kidney Transplantation-a Pilot Study1

Abstract: Hyperlipidemia is an important complication of kidney transplantation affecting up to 74% of recipients. HMG-CoA reductase inhibitors are reported to provide safe and effective treatment for this problem. A recent study suggests that pravastatin, an HMG-CoA reductase inhibitor, also decreases the incidence of both clinically severe acute rejection episodes and natural killer cell cytotoxicity after orthotopic heart transplantation. We have performed a prospective randomized pilot study of the effect of pravast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
117
2
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(129 citation statements)
references
References 28 publications
4
117
2
6
Order By: Relevance
“…We demonstrate that the HMG-CoA reductase inhibitor atorvastatin reduces ␥IFN-induced RMEC DR expression in vitro; however, our donor population did not allow us to answer the question of whether or not statins affect RMEC HLA-DR expression in vivo, because none of the donors were taking statins at the time of nephrectomy. Statins have been associated with a reduced rate of rejection in kidney transplants (49,50), although the mechanism for this effect has not been delineated. Although it is possible that statins may affect HLA class II expression on RMEC, the benefit of this under normal physiologic conditions depends on whether or not RMEC are capable of promoting an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that the HMG-CoA reductase inhibitor atorvastatin reduces ␥IFN-induced RMEC DR expression in vitro; however, our donor population did not allow us to answer the question of whether or not statins affect RMEC HLA-DR expression in vivo, because none of the donors were taking statins at the time of nephrectomy. Statins have been associated with a reduced rate of rejection in kidney transplants (49,50), although the mechanism for this effect has not been delineated. Although it is possible that statins may affect HLA class II expression on RMEC, the benefit of this under normal physiologic conditions depends on whether or not RMEC are capable of promoting an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of statins specific to the transplant population that have been demonstrated previously include favorable effects on cardiac events (13), chronic and acute rejection (23,24), and associations with improved patient survival (25), lower blood pressure (26) and improved bone mineral density (27). In this study it has been demonstrated that statins have a favorable influence on the development of new-onset diabetes after transplantation as well.…”
Section: Discussionmentioning
confidence: 99%
“…Two small initial randomized controlled trials (RCTs) investigating statins for prevention of allograft kidney rejection showed significantly lower rejection rates in statin-treated patients (140,141). However, 3 subsequent RCTs demonstrated no significant differences between short-term rejection rates between 400 ABELES AND PILLINGER patients in the intervention and control arms (142)(143)(144).…”
Section: Statin Trials In Human Inflammatory and Autoimmune Diseasesmentioning
confidence: 99%